Do bankers discriminate against women entrepreneurs? - Mahmood, Rosli; Bidin, Asiah; Bakar, Habshah (Institut Bank-Bank Malaysia, 2002)
THERE HAS BEEN a significant increase in the number of businesses started by women in the last decade.This growth has been accompanied by a similar increase in studies on women entrepreneurship that focused largely on problems and challenges faced by women entrepreneurs.Among the issues that have been highlighted is that of getting access to bank financing.Studies have found that many women who wanted to go into business were hampered by their inability to secure loans from the banks.These women often claimed that they were discriminated against in both overt and subtle ways.Hisrich (1985) asserts that while financing is a problem for every entrepreneur, for women entrepreneurs the problem is more acute.Thus, women entrepreneurs are less likely to use formal sources of capital such as bank loans.While explicit evidence on this inequitable lending practice has yet to be produced, certain statements have been made which implied that there might be gender-based discrimination that occurs among bankers (Orhan, 2001).This prompted a call from a woman Cabinet member for separate banking counters for women entrepreneurs applying for loans (The Star, 2001).This paper aims to provide further evidence by conducting a study among women entrepreneurs in Malaysia on the extent to which gender may be the issue in the relationship with the banks.